Role of Plasma Membrane NADPH Oxidase in Response to Salt Stress in Cucumber Seedlings - Katarzyna Kabała; Małgorzata Reda; Anna Wdowikowska; Małgorzata Janicka (MDPI AG, 2022)
Plasma membrane NADPH oxidases (RBOHs, EC 1.6.3.1) are known as the main ROS generators involved in plant adaptation to stress conditions. In the present work, regulation of NADPH oxidase was analyzed in cucumber (Cucumis sativus L. var. Krak) seedlings exposed to salinity. RBOH activity and gene expression, as well as H2O2 content, were determined in the roots of plants treated with 50 or 100 mM NaCl for 1 h, and 50 mM NaCl for 1 or 6 days. It was found that enzyme activity increased in parallel with an enhancement in the H2O2 level in roots exposed to 100 mM NaCl for 1 h, and to 50 mM NaCl for 1 day. The expression of some CsRboh genes was induced by salt. Moreover, an increase in the activity of G6PDH, providing the substrate for the NADPH oxidase, was observed. In seedlings subjected to salinity for a longer time, antioxidant enzymes-including superoxide dismutase, catalase, and ascorbate peroxidase-were activated, participating in maintaining a steady-state H2O2 content in the root cells. In conclusion, NADPH oxidase and endogenous H2O2 up-regulation seem to be early events in cucumber response to salinity.